2022
DOI: 10.3390/cancers14051142
|View full text |Cite
|
Sign up to set email alerts
|

Expression of miR-24-1-5p in Tumor Tissue Influences Prostate Cancer Recurrence: The PROCA-life Study

Abstract: The role of miR-24-1-5p and its prognostic implications associated with prostate cancer are mainly unknown. In a population-based cohort, the Prostate Cancer Study throughout life (PROCA-life), all men had a general health examination at study entry and were followed between 1994 and 2016. Patients with available tissue samples after a prostatectomy with curative intent were identified (n = 189). The tissue expression of miR-24-1-5p in prostate cancer was examined by in situ hybridization (ISH) in tissue micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Such results were independently validated in yet another study with RP specimens from 475 patients 34 . Moreover, levels of several other miRNAs assessed in RP samples (in tumour and/or adjacent tissue) also associated with BCR, some even after adjusting for classical clinicopathological variables 35–46 …”
Section: Prostate Cancermentioning
confidence: 64%
See 1 more Smart Citation
“…Such results were independently validated in yet another study with RP specimens from 475 patients 34 . Moreover, levels of several other miRNAs assessed in RP samples (in tumour and/or adjacent tissue) also associated with BCR, some even after adjusting for classical clinicopathological variables 35–46 …”
Section: Prostate Cancermentioning
confidence: 64%
“…34 Moreover, levels of several other miRNAs assessed in RP samples (in tumour and/or adjacent tissue) also associated with BCR, some even after adjusting for classical clinicopathological variables. [35][36][37][38][39][40][41][42][43][44][45][46] Serum miR-146b-3p was a significant predictor of time to BCR, independent of clinicopathological parameters. 47 in patients treated by RP.…”
Section: Can Mirnas Predict Biochemical Recurrence/clinical Recurrenc...mentioning
confidence: 91%
“…This list of 92 cnvd -miRNAs was an assortment of novel predictive candidates and acknowledged markers of radiation and cancer. For instance, miR-24-1-5p 64 , miR-30e-3p 65 , miR-28-5p 66 , miR-142-3p 67 , miR-148a-5p 68 , miR-455-3p 69 , miR-139-3p 70 , miR-1306-5p 71 and several others mentioned in Table 1 were linked to various radiation and carcinogenesis studies. On the other hand, there are some candidates in the list of 92 cnvd -miRNAs, such as miR-30a-3p and miR-199b-5p, which had not previously linked to minipig radiation model.…”
Section: Discussionmentioning
confidence: 99%
“…However, the functional research on miR-24-1-5p is still in the exploratory stage. Stikbakke et al found that high expression of miR-24-1-5p is associated with an increased risk of prostate cancer recurrence after radical prostatectomy, indicating its potential diagnostic and therapeutic value in prostate cancer cases [40]. Overexpression of miR-24-1-5p in human colorectal cancer cells signi cantly inhibits β-catenin expression and reduces cell proliferation, migration, and survival [41].…”
Section: Disscussionmentioning
confidence: 99%